2004
DOI: 10.1111/j.1365-313x.2004.02237.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of glycinebetaine synthesis in tomato protects seeds, plants, and flowers from chilling damage

Abstract: Tomato (Lycopersicon esculentum Mill.) plants, which normally do not accumulate glycinebetaine (GB), are susceptible to chilling stress. Exposure to temperatures below 10 degrees C causes various injuries and greatly decreases fruit set in most cultivars. We have transformed tomato (cv. Moneymaker) with a chloroplast-targeted codA gene of Arthrobacter globiformis, which encodes choline oxidase to catalyze the conversion of choline to GB. These transgenic plants express codA and synthesize choline oxidase, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(147 citation statements)
references
References 57 publications
5
141
0
1
Order By: Relevance
“…Titration. All experiments were performed in the presence of betaine, a natural osmolyte, at pH 7.0, because it has previously been shown that PS II preparations are more stable in the presence of 1 M glycine betaine (12,(38)(39)(40)(41)(42)(43). Details of the physiological conditions used for various species are summarized in SI Materials and Methods, Figs.…”
Section: Methodsmentioning
confidence: 99%
“…Titration. All experiments were performed in the presence of betaine, a natural osmolyte, at pH 7.0, because it has previously been shown that PS II preparations are more stable in the presence of 1 M glycine betaine (12,(38)(39)(40)(41)(42)(43). Details of the physiological conditions used for various species are summarized in SI Materials and Methods, Figs.…”
Section: Methodsmentioning
confidence: 99%
“…In COD-transgenic tomato plants, GB showed an effect on chilling stress tolerance (Park et al 2004). Despite very low GB accumulation, the transgenic tomato plants exhibited enhanced chilling tolerance at all developmental stages, from seed germination to the reproductive stage.…”
Section: Effect Of Gb On Low Temperaturesmentioning
confidence: 99%
“…Despite very low GB accumulation, the transgenic tomato plants exhibited enhanced chilling tolerance at all developmental stages, from seed germination to the reproductive stage. The enhanced chilling-stress tolerance in the presence of very low GB levels may be due to the very low threshold level of endogenous GB (Ͼ0.1 mmol g Ϫ1 fw) that is sufficient to provide full protection against chilling stress in transgenic tomato (Park et al 2004). In addition, both cytosolic and chloroplast-targeted COD-transgenic tomato plants showed a correlation between the accumulated GB in these compartments and the degree of tolerance to low temperature, salt, and oxidative stresses (Park et al 2007a).…”
Section: Effect Of Gb On Low Temperaturesmentioning
confidence: 99%
“…For switchgrass seeds, published colorimetric methods for determining tissue peroxide levels (Park et al 2004;Cheeseman 2006) were unsuccessful primarily due to a high background arising from extractable components that interfered with these assays. Attempts to clean extracts by passage through normal or C-18 reverse phase matrices conditioned with phosphate buVer containing 5 mM KCN (Cheeseman 2006) were also unsuccessful.…”
Section: Confocal Microscopymentioning
confidence: 99%